ATTITUDINAL BARRIERS TOWARDS DISABLED PEOPLE IN SOCIETY - G. V. Zhigunova; I. L. Tkachenko (Вестник университета)
The inclusion of people with disabilities in social processes is an important task of modern society, due to the implementation of the provisions of the Convention on the equal rights of persons with disabilities. However, the achievement of this task is hampered by the presence of inclusive barriers in society, an important place of which is occupied by attitudinal barriers. The article presents the results of author’s sociological research (expert survey) on the example of Murmansk region of Russian Federation, which has revealed the most vulnerable category of persons with disabilities from the point of view of its perception by the society and raised the issue of the ways of forming of tolerant attitude of society and achievement of the social integration of citizens. The obtained data are important for the development of effective measures to eliminate attitudinal barriers, impeding the processes of social integration.